Pengaruh Penggunaan Model Discovery Learning Berbantuan Media Audiovisual terhadap Keterampilan Menulis - Intania, Dwi Putri; R, Syahrul (Al-DYAS, 2023)
The purpose of this study was to describe the effect of using a discovery learning model assisted by audiovisual media on the skills of writing explanatory texts for class XI students of SMAN 1 Sungai Tarab. This type of research is a quantitative research with a quasi-experimental method of the one group pretest-posttest design. Based on the results of the study concluded the following three things. First, the skills of writing explanatory texts for class XI students of SMAN 1 Sungai Tarab before using the audiovisual media-assisted discovery learning model are in the Adequate qualification (LdC) with an average value of 67.24. Second, the skills of writing explanatory texts for class XI students of SMAN 1 Sungai Tarab after using the audiovisual media-assisted discovery learning model are in the Good qualification (B) with an average value of 83.87. Third, based on the t-test, the alternative hypothesis (H1) is accepted at the level of confidence and degrees of freedom (dk) = (n-1) because tcount>ttable (6.40>1.70). In other words, the discovery learning model assisted by audiovisual media influences the skills of writing explanatory texts for class XI students of SMAN 1 Sungai Tarab.